Dynamics of Public Policy in the Digital Era: A Case Study of e-Government Implementation in Indonesia - Permana, Danny (Global Writing Academica Researching and Publishing, 2023)
This article examines the evolving dynamics of public policy in Indonesia in the context of the digital era, with a focus on the implementation of e-Government initiatives. It aims to analyze how digital technologies are reshaping public policy, particularly in terms of enhancing government efficiency and transparency. Utilizing a case study approach, the research delves into the processes and outcomes of e-Government projects in Indonesia, identifying key factors that influence their success and challenges faced. The findings highlight the implications of digital integration in public administration and offer insights into the strategic approaches adopted for e-Government implementation. This study contributes to the broader understanding of digital transformation in governance, emphasizing its impact on policy-making processes and public service delivery in a developing country context. The conclusions drawn from this research provide valuable recommendations for policymakers and practitioners involved in the digitalization of public services and underline the need for continued innovation and adaptation in the face of technological advancements.